KEMUDAHAN, KEPERCAYAAN DAN PERSEPSI RESIKO TERHADAP KEPUTUSAN PEMBELIAN PENGGUNA DOMPET DIGITAL OVO DI SURAKARTA - Indriyani Kusumawati; Sri Hartono; Eny Kustiyah (Universitas Nusa Cendana, 2020)
A purchasing decision is a process of taking an opinion when making a product purchase. Thisresearch aims to know the simultaneous and partial relationships among Simplicity, Trust andRisk Perception to Purchasing Decisions of the OVO digital wallet users in Surakarta. The methodof research is quantitative descriptive research design. The sampling technique is the purposivesampling method. Data was taken directly using a questionnaire of 100 respondents. The analyticalmethods used in the study is Multiple Linear Regression Analyses. The results showed thatSimplicity, Trust and Risk Perception variables simultaneously & significantly impact onPurchasing Decision. Partially, Simplicity and Trust have positive and significant influence toPurchasing Decision while Risk Perception has no significant effect.Keywords: Simplicity, Trust, Risk Perception, Purchasing Decision